2020
DOI: 10.3389/fpls.2020.599904
|View full text |Cite
|
Sign up to set email alerts
|

The Soil Nutrient Environment Determines the Strategy by Which Bacillus velezensis HN03 Suppresses Fusarium wilt in Banana Plants

Abstract: Biological control agents (BCAs) are considered as one of the most important strategies for controlling Fusarium wilt, and bioorganic fertilizer, in particular, has been extensively investigated. However, little is known regarding how a biocontrol microorganism affects the suppression mechanisms when combined with different amendments. In this study, a pot experiment was performed using banana plants to investigate the different mechanisms by which the biocontrol bacterium Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…From an ecological point of view, biological control agents are often influenced by environmental factors, including the availability of nutrients and other microbes in the ecosystem. The combination of Bacillus velezensis HNO 3 with worm compost or cow dung has been shown to increase the suppression of Fusarium wilt in banana plants due to the high accumulation of several elements, such as Mg, P, Zn and Mn (Wu, Shan, Li, Li, & Wu, 2020). The other indirect mechanism may also be involved in suppressing this disease due to the addition of some mineral elements contained in CSP, including Ca, P, Zn, and K as reviewed by Orr & Nelson (2018).…”
Section: Effects Of Treatments On Disease Developmentmentioning
confidence: 99%
“…From an ecological point of view, biological control agents are often influenced by environmental factors, including the availability of nutrients and other microbes in the ecosystem. The combination of Bacillus velezensis HNO 3 with worm compost or cow dung has been shown to increase the suppression of Fusarium wilt in banana plants due to the high accumulation of several elements, such as Mg, P, Zn and Mn (Wu, Shan, Li, Li, & Wu, 2020). The other indirect mechanism may also be involved in suppressing this disease due to the addition of some mineral elements contained in CSP, including Ca, P, Zn, and K as reviewed by Orr & Nelson (2018).…”
Section: Effects Of Treatments On Disease Developmentmentioning
confidence: 99%
“…Previous studies have suggested that some nutrient elements in banana plants and their associated soils can reduce the severity of plant diseases by increasing disease tolerance and resistance against plant pathogens ( Dordas, 2008 ; Siddiqui et al, 2015 ; Wu et al, 2020 ). There were positive correlations observed between the contents of Zn, Mn, Mg, and P in banana and the suppression of wilt disease severity ( Wu et al, 2020 ). In present study, the nutrient uptake ratio of N:P:K:Ca:Mg:S were 1:0.13:3.86:0.68:0.40:0.07 (Zhongjiao No.…”
Section: Discussionmentioning
confidence: 99%
“…Banana Fusarium wilt is caused by vascular wilt pathogens, which satisfy their nutritional requirements by efficiently acquiring the scarce nutrients available in the xylem sap, by enzymatic digestion of host cell walls, by invading neighboring cells, or by inducing nutrient leakage from surrounding tissues ( Divon et al, 2005 ; Möbius & Hertweck, 2009 ; Klosterman et al, 2011 ; Yadeta & Thomma, 2013 ). High Mg accumulations could enhance plant suppression to Foc4 ( Wu et al, 2020 ). Therefore, the absorption and accumulation of Mg may be a key mechanism related to nutrient element modulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations